Phytochemical Analysis of Saponifiable Matter of Petroleum Ether Extract of Leaves of Butea monosperma - P. Rajput, Ambarsing; S. Patil, Bhagavan (Asian Journal of Chemistry, 2013)
The present study designed for phytochemical analysis, antibacterial, antifungal activity of saponifiable matter of petroleum ether extract of leaves of Butea monosperma belongs to family Fabaceae. The extraction preformed by soxhlet extractor and identification was performed by phytochemical test. The petroleum ether extract of leaves of Butea monosperma was saponified using 1 M alcoholic KOH, to separate saponifiable (fatty material) and unsaponofibale matter. A comprehensive phytochemical investigation of the saponifiable matter of petroleum ether extract of leaves of Butea monosperma resulted in the isolation and identification of four known compounds Palmitic acid, tetradecanoic acid, oleic acid and a-linolenic acid. To our best of knowledge, these four compounds were isolated from leaves of plant for the first time. Their structures were identified by physical, chemical, elemental analysis and spectroscopic methods including UV, FTIR, MS, 1H NMR, 13C NMR. The study was further continued for screening of antibacterial activity against E. coli, P. aeruginosa, B. subtilis, S. aureus and antifungal activity screened against A. niger and C. albicans using agar diffusion assay.